Arrhythmia and/or Cardiomyopathy Related to Maternal Autoantibodies: Descriptive Analysis of a Series of 16 Cases From a Single Center - Wang, Benzhen; Hu, Sujuan; Shi, Degong; Bing, Zhen; Li, Zipu (Frontiers in Pediatrics, 2019)
Objective: To describe the clinical characteristics of maternal autoantibody-mediated arrhythmia and/or cardiomyopathy, and explore the therapeutic role of glucocorticoids. Methods: This is a retrospective observational study of fetuses and children presenting with autoantibody-mediated arrhythmia and/or cardiomyopathy in our hospital from September 2010 to December 2018. Results: 16 patients were identified, including two fetuses and fourteen children. one mother suffered from Sjogren's syndrome, two systemic lupus erythematosus (SLE), and the remaining thirteen were asymptomatic carriers of autoantibodies. 2 fetuses were diagnosed with complete congenital heart block (CHB) that mean heart rate was 45bpm and 50bpm respectively. In fourteen surviving children, third-degree CHB were detected in 4 children, second- to third-degree CHB in 4, QTc prolongation in 1, atrioventricular dissociation and junctional ectopic tachycardia in 1, complete left bundle branch block (CLBBB) with dilated cardiomyopathy (DCM) in 3 and endocardial fibroelastosis (EFE) in 1. All the surviving babies received intravenous immunoglobulin and glucocorticoid. None of the children had received the pacemaker implantation. During follow-up, one 3-month-old girl who had complete CHB, DCM and Torsades de pointes almost recovered after the administration of prednisone for about 8 years. three cases with complete CHB had no improvement. One case with EFE and three cases with CLBBB and DCM were in stable condition. Children with QTc prolongation and junctional ectopic tachycardia respectively returned to a regular rhythm. Conclusions: Autoantibody-mediated arrhythmias and/or cardiomyopathy are severe complications related to maternal autoantibodies, and the administration of steroid may have the effect to reverse complete CHB.